Engaging Employees in Management and Decision-Making Process: A Case Study on “Vision Garments Limited” - Most. Tahura Pervin; Razia Begum (Goodwood Publishing, 2022)
Purpose: The key aim of this study was to understand the employee engagement (EE) practice in decision-making from Vision Garment Limited's (VGL) perspective. Research Methodology: Two focus group discussions (FGDs) were conducted based on judgmental sampling to understand the real scenario from two crucial viewpoints. Result: The study revealed employee engagement (EE) practice in decision-making exists in VGL. The key challenges were identified as proper knowledge and qualification, physical dispersion among the parties in some cases, middlemen between the parties, mutual understanding and respect, unwillingness to delegate power, and nonexistence or nonfunctioning of the plant-level trade union. Limitation: The study was just an exploratory type hence some descriptive results based on the above variables need to be explored. In addition, a few causal relationships among the variable can also be tested in this particular research domain. Originality: Most of the earlier researchers could not address Plant level Trade Unionism (TU) can be considered a platform of EE practice. However, this research has addressed the issue as evidence from the real-life investigation. In addition, the garment firms may allow the specialized garment business-related TU practice at the micro-level as a platform for their EE practice.